2016
DOI: 10.1074/jbc.m116.736389
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Deinococcus radiodurans RecA Regulates Its Activity and May Contribute to Radioresistance

Abstract: Deinococcus radiodurans has a remarkable capacity to survive exposure to extreme levels of radiation that cause hundreds of DNA double strand breaks (DSBs). DSB repair in this bacterium depends on its recombinase A protein (DrRecA). DrRecA plays a pivotal role in both extended synthesis-dependent strand annealing and slow crossover events of DSB repair during the organism's recovery from DNA damage. The mechanisms that control DrRecA activity during the D. radiodurans response to ␥ radiation exposure are unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 45 publications
1
46
0
1
Order By: Relevance
“…For instance, DdrO (DR_2574) has been identified as a repressor of gene expression, which upon cleavage by PprI (IrrE) depresses the expression of DNA damage response genes (39). Regulation of RecA activity by phosphorylation has been demonstrated recently (40). It has been shown that RecA and PprA of D. radiodurans are phosphorylated by a DNA damage response protein kinase and that the phosphorylation of these proteins affects their functions both in vivo and in vitro (40,41).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, DdrO (DR_2574) has been identified as a repressor of gene expression, which upon cleavage by PprI (IrrE) depresses the expression of DNA damage response genes (39). Regulation of RecA activity by phosphorylation has been demonstrated recently (40). It has been shown that RecA and PprA of D. radiodurans are phosphorylated by a DNA damage response protein kinase and that the phosphorylation of these proteins affects their functions both in vivo and in vitro (40,41).…”
Section: Figmentioning
confidence: 99%
“…Regulation of RecA activity by phosphorylation has been demonstrated recently (40). It has been shown that RecA and PprA of D. radiodurans are phosphorylated by a DNA damage response protein kinase and that the phosphorylation of these proteins affects their functions both in vivo and in vitro (40,41). These mechanisms, however, could explain the gamma radiationinducible expression of only some of the genes in the absence of a canonical SOS response.…”
Section: Figmentioning
confidence: 99%
“…It is likely that SSB is dephosphorylated during the DNA damage response, modulating its binding to DNA and allowing RecA-dependent DNA repair to occur. In another paradigm of DNA damage responses with Deinococcus radiodurans, phosphorylation of RecA at Tyr77 and additionally at Thr318 modifies the activity of RecA by increasing its affinity for double-stranded DNA (dsDNA) (40). It is unclear whether this occurs for RecA homologues in other bacteria, although the above examples of tyrosine phosphorylation of DNA binding proteins involved in DNA repair and recombination mechanisms warrant a fresh look at the dynamic nature of stress responses in bacteria.…”
Section: Stress Responses Involving Tyrosine Phosphorylationmentioning
confidence: 99%
“…DSBs are major lesions induced by irradiation , and the DSB repair capacity is closely related to radiosensitivity . Because RPA3 reportedly participates in the HR of DSBs , we evaluated the DNA damage response induced by 2 Gy of irradiation in these cells.…”
Section: Resultsmentioning
confidence: 99%